Implementing and assessing organizational practices in local health departments. - Turnock, B J (1994)
One of the most difficult forms of public health practice to characterize involves governmental public health agencies, especially at the local level. A lack of consensus within the public health community as to the purpose and content of organizational public health practice inhibits efforts to increase the capability of public health to address effectively its core functions of assessment, policy development, and assurance. Meaningful capacity building efforts must establish both benchmarks and expectations for the organizational practice of public health. Those markers must be established so that the impact of practice on outcomes and health status can be examined. A model identifying 10 organizational practices was established through the work of the Centers for Disease Control and Prevention (CDC) in collaboration with national practice organizations. Early applications of the model to public health capacity building activities have been effective. Among the applications have been approaches to surveillance of health department practice, certification of local health departments using practice guidelines, and development of leadership within the public health enterprise. Although results are promising, use of the model requires additional external examination and validation, as well as acceptance and consensus within the public health community. The development of organizational practice guidelines for public health agencies may be useful in further efforts to characterize and measure public health practice and its impact on the public's health.